Implementation of the Implementation of Hallucination Implementation Strategies Related to the Readiness of Nursing Centers for the Integrated Emergency Management System (SPGDT) at the Palembang Homeless and Displaced Persons’ Home - Inne Yelisni; Ayu Dekawaty; Meriyatul Rahmi (Jurnal Inspirasi Kesehatan, 2023)
In Indonesia, the problem of mental disorders is still a considerable burden of disease. Mental health problems in Indonesia are very important public health problems and must receive serious attention from all levels of government across sectors, both at the central and regional levels, as well as the attention of the whole community. Hallucinations are one of the mental disorders in which a person is unable to distinguish between real life and fake life. It is intended that the implementation of nursing services meets service standards. The steps of these activities are in the form of Standard Operating Procedures (SOP). The purpose of this study was to analyze the Implementation of Hallucination Implementation Strategies related to the Readiness of Nursing Centers for the Integrated Emergency Management System (SPGDT) at the Palembang Homeless and Displaced Persons' Home. The research method used is qualitative research with in-depth interviews and observation. Informants in the study amounted to 10 people consisting of the head of the orphanage, mental nurses who were in the Homeless Home and Palembang displaced people. The variables used to look at the implementation of these policies are communication, resources, disposition, bureaucratic structure and environment. The research will be carried out for 3 months June-Agust 2023. Data analysis is processed according to characteristics with content analysis, namely: Data collection, Reduction data, verification, presentation of data and drawing conclusions. It is hoped that the results of this study will serve as an evaluation of the implementation of Hallucination Implementation Strategies related to the Readiness of Nursing Homes for the Integrated Emergency Management System (SPGDT).